Performance Comparison of Thin and Thick Film Microstrip Rejection Filters - M. M. Mandhare; S. A. Gangal; M. S. Setty; R. N. Karekar (Active and Passive Electronic Components)
A performance comparison of microstripline circuits using thin and thick film techniques has been studied, in which a Microstrip rejection filter, in the X-band of microwaves, is used as test circuit. A thick film technique is capable of giving good adhesive films with comparable d.c. sheet resistivity, but other parameters such as open area (porosity), particle size, and edge definition are inferior to thin-film microstrip filters. Despite this drawback, the average value of transmission, transmission loss, reflection coefficient, resonant rejection frequency, and quality factor for thick-film filters indicate that screen printed Ag films are intermediate between thin-film1,2,9 and etched-thick-film9 microstrip filters in performance, making it a feasible method for microstrip circuits.